Pole length affects O2-cost and performance in double poling - Losnegard, T.; Myklebust, H.; Skattebo, O.; Stadheim, H. K.; Sandbakk, O.; Hallén, J. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: In double poling (DP), propulsive forces are transferred only thru the poles. Pole length in the classical style is normally ~84% of body height although studies report beneficial effect of longer poles (~88%) during short duration tests on snow (Hansen & Losnegard 2010). This study aimed to identify the effect of longer poles on O2-cost, cycle characteristics and performance during DP and in the diagonal stride (DIA) on a roller ski treadmill.